Driving Aceh’s Economic Growth through Digital Finance and MSME Credit: Empirical Evidence - Yasrizal Yasrizal; Mahrizal; Said Mahdani; Sailal Arimi; Sri Rosmiati Sani (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose: This study examines district/city-level economic growth in Aceh Province by analyzing the roles of financial inclusion, MSME credit, payment digitalization, inflation, and unemployment. It highlights that regional growth is increasingly shaped by the productive use of financial services and digital payment systems, not merely by financial access. Design/methodology/approach: This study employs a quantitative approach using balanced panel data from 23 districts/cities in Aceh Province during 2020–2025, yielding 138 observations. The analysis applies a Fixed Effects Model and uses Driscoll-Kraay robust standard errors to correct for heteroskedasticity, serial autocorrelation, and cross-sectional dependence. The 2025 observations are treated as projected data estimated using linear trend extrapolation based on the latest available official data. The projected variables include economic growth, financial inclusion, payment digitalization, MSME credit, inflation, and unemployment. Findings: The findings indicate that payment digitalization shows the strongest positive association with district/city-level economic growth in Aceh Province. MSME credit is also positively associated with regional growth, while unemployment shows a negative association. Inflation is positively associated with growth during the study period, possibly reflecting demand-driven economic activity. Financial inclusion shows a negative and statistically significant coefficient, suggesting that financial access has not yet been effectively transformed into productive financial use. Originality/value: This study contributes to the regional finance-growth literature by showing that payment digitalization is a stronger driver of district/city-level economic growth than general financial inclusion. The findings emphasize that financial access alone is insufficient unless it is transformed into productive-use inclusion through digital payments, MSME financing, and employment-oriented policies.